Stressing Mitosis to Death - Burgess, Andrew; Rasouli, Mina; Rogers, Samuel (Frontiers in Oncology, 2014)
The final stage of cell division (mitosis), involves the compaction of the duplicated genome into chromatid pairs. Each pair is captured by microtubules emanating from opposite spindle poles, aligned at the metaphase plate, and then faithfully segregated to form two identical daughter cells. Chromatids that are not correctly attached to the spindle are detected by the constitutively active spindle assembly checkpoint (SAC). Any stress that prevents correct bipolar spindle attachment, blocks the satisfaction of the SAC, and induces a prolonged mitotic arrest, providing the cell time to obtain attachment and complete segregation correctly. Unfortunately, during mitosis repairing damage is not generally possible due to the compaction of DNA into chromosomes, and subsequent suppression of gene transcription and translation. Therefore, in the presence of significant damage cell death is instigated to ensure that genomic stability is maintained. While most stresses lead to an arrest in mitosis, some promote premature mitotic exit, allowing cells to by-pass mitotic cell death. This mini-review will focus on the effects and outcomes that common stresses have on mitosis, and how this impacts on the efficacy of mitotic chemotherapies.